2010
DOI: 10.1590/s1413-86702010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infections in renal transplant recipients

Abstract: We declare no conflict of interest. ABSTRACTThe impact of intestinal parasitic infection in renal transplant recipients requires careful consideration in the developing world. However, there have been very few studies addressing this issue in Iran. This study was conducted to determine the prevalence of intestinal parasitic infections in renal transplant recipients in Iran. Stool specimens from renal transplant recipients and control groups were obtained between June 2006 and January 2007. The samples screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…A study conducted in Iran showed that multiple parasitic infections were more frequent in immune-compromised patients than controls, indicating that reduced immunity facilitated establishment of STH infection [33]. Again, future studies of immune status in podoconiosis would be useful in exploring this relationship further.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Iran showed that multiple parasitic infections were more frequent in immune-compromised patients than controls, indicating that reduced immunity facilitated establishment of STH infection [33]. Again, future studies of immune status in podoconiosis would be useful in exploring this relationship further.…”
Section: Discussionmentioning
confidence: 99%
“…Among these patients, a large group of organ transplant recipients, patients taking corticosteroid drugs and chemotherapy, patients with cancer, acquired immune deficiency syndrome (AIDS) patients, and people undergoing radiation therapy as well as patients undergoing hemodialysis can be pointed. 6,7 With more than 95% of kidney damage, accumulation of toxins in the body is increased sufficiently and sustaining life would not be possible without the use of dialysis or kidney transplant. 8 Several reports indicate that populations with renal dysfunction requiring dialysis are rising.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal protozoan parasitosis seems to be more common among transplant recipients compared to non-transplanted control subjects [ 134 ]: even parasites that are largely asymptomatic before transplantation may become clinically evident under immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to determine the exact etiology of the diarrhea in these patients, including drug-specific effects (i.e., mycophenolate mofetil, antibiotics, colchicines, laxative drug), metabolic conditions, mechanical complications of surgery, acute GVHD, as well as infectious agents (bacteria, such as Clostridium difficile , Campylobacter jejuni , Shigella sonnei and Salmonella enteritidis and virus, first of all CMV, but also Rotavirus, and parasites, in particular protozoan agents such as Cryptosporidium spp., Blastocystis spp., Giardia duodenalis , Entamoeba histolytica , Entamoeba coli , Endolimax nana , Iodamoeba butschili , Chilomastix mesnili , and Microsporidia spp.) [ 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation